Perfectionism as Predictor of Psychological Wellbeing among College Students (Global Journal of Human-Social Science, 2016)
India is a collectivistic society that places considerable amount of importance on its members to strive for the best as every action, desire, accomplishment and failure has social connotations for family and other close members of society. There are social pressures to achieve and to be perfect. This has a direct implication on the wellbeing of an individual especially college students since they are in the transition phase wherein they are looking for meaning in life in terms of right career choices and making their parents proud. The present study explored perfectionism and psychological wellbeing among college students and their interrelationship. A total of 281 college students (Males=174, Females= 107) in the age range of 18-24 years, participated in the study. They were administered Multidimensional Perfectionism Scale and Ryff's Scale of Psychological Wellbeing. Results revealed that all the three dimensions of perfectionism show significant relationship with all the six dimensions of psychological wellbeing. Perfectionism, both self oriented and socially prescribed, accounted for a large variance in many dimensions of psychological wellbeing.
Keywords: perfectionism; psychological wellbeing; college student